INTEGRASI AI DALAM PENULISAN BERITA MAHASISWA:: DAMPAKNYA TERHADAP KREATIVITAS DAN ETIKA JURNALISTIK - Umi Kulsum; Zainah Asmaniah; Syifa Purwati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study was motivated by the increasing use of artificial intelligence (AI) in students’ news writing. While AI offers efficiency in generating texts quickly, it also raises concerns about creativity and journalistic ethics. The study aimed to describe the integration of AI in students’ news writing and to analyze its impact on creativity and journalistic ethics. A mixed-method approach with descriptive and associative design was employed. The participants were students of the Indonesian Language and Literature Education Program. Data were collected through a Likert-scale questionnaire, document analysis of students’ news texts, semi-structured interviews, and observation. Quantitative data were analyzed descriptively and correlationally, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings show that AI integration in news writing was in the high category. The use of AI helped students develop ideas, determine news angles, and organize texts more systematically. In addition, students’ journalistic ethics were categorized as good, particularly in terms of information verification, responsibility for content, and awareness of avoiding direct use of AI-generated output. This study concludes that AI integration can support students’ creativity and journalistic ethics when it is used critically, proportionally, and responsibly.